2010
DOI: 10.1097/sla.0b013e3181c9b55a
|View full text |Cite
|
Sign up to set email alerts
|

The Migration of Surgeons

Abstract: This study attempted to determine if there were identifiable trends in where surgeons moved from and to over time. Physicians, including surgeons, change the location of their practices over their careers. If this movement follows economic theory that surgeons, like most professionals, seek better economic opportunities, then their movements should be toward better markets for their services. Using US national data (American Medical Association Masterfile) that describes the practice locations of surgeons, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…With regard to the research on skilled migrant careers, research attention has concentrated almost exclusively on careers within the medical and scientific professions (e.g. Bourgeault, Neiterman, & LeBrun, 2011;Fang, 2007;Girasek, Molnar, Eke, & Szócska, 2011;Hardill & MacDonald, 2000;Ricketts, 2010;Roberts & Simmons, 2009). However, skilled migrants do not feature as 'talents' in any of this literature, and success stories of skilled migrants are lacking (Crowley-Henry et al, 2016).…”
Section: Understanding the Tm Of Skilled Migrantsmentioning
confidence: 99%
“…With regard to the research on skilled migrant careers, research attention has concentrated almost exclusively on careers within the medical and scientific professions (e.g. Bourgeault, Neiterman, & LeBrun, 2011;Fang, 2007;Girasek, Molnar, Eke, & Szócska, 2011;Hardill & MacDonald, 2000;Ricketts, 2010;Roberts & Simmons, 2009). However, skilled migrants do not feature as 'talents' in any of this literature, and success stories of skilled migrants are lacking (Crowley-Henry et al, 2016).…”
Section: Understanding the Tm Of Skilled Migrantsmentioning
confidence: 99%
“…In many specialties including dermatology, market forces never have completely ameliorated workforce maldistribution problems. [6][7][8][9][10][11] Dermatologists emerging from training report that geographic location is the top factor in evaluating potential job opportunities and that they are usually able to find plentiful op-portunities in preferred locations. 12 If an underserved area also is seen as undesirable, it may struggle to attract dermatologists, even if it boasts strong patient demand and outstanding job opportunities with relatively high compensation.…”
Section: T He Dermatology Work-mentioning
confidence: 99%
“…On an empirical basis, Cooper et al [ 21 ] showed on a macro-level that economic development is positively associated with physician supply as well as with related utilization. The studies from Ricketts and Randolph [ 22 ], Ricketts [ 23 ], and Ricketts [ 24 ] analyzed what factors of departure- and destination-district as well as physician characteristics influence the decision of practice location by moving physicians.…”
Section: Introductionmentioning
confidence: 99%